A combined multi-objective multi criteria approach for blockchain-based synchromodal transportation. (February 2023) - Oudani, Mustapha
Abstract: Despite our planet's serious environmental challenges, road transportation remains the most important mode of freight shipment, with the broadest coverage and the greatest influence on global economic development. Intermodal transportation may be a more environmentally friendly alternative to heavy road use. However, such a solution is still limited in terms of scalability, service quality, and interoperability. In this context, synchromodal transportation combined with block chain technology may play a critical role in achieving transportation system efficiency and sustainability. In this paper, we study the use of blockchain technology for synchromodal transportation. We build a multi-objective mathematical model for the optimization of transportation cost, transportation time, C O 2 emissions and the blockchain cost. Then, we use several variants of the well-known weighting method and epsilon constraints method to get compromise solutions. We rank the obtained compromise solutions using a variety of multi-criteria decision methods. Then a metaranking method is used to obtain an aggregated ranking. Results show that the proposed methodology may help to ensure the security, the efficiency and the sustainability of synchromodal transportation. Highlights: A multi-objective program is proposed for the synchromodal transportation. Blockchain cost is integrated as a component in the optimization model. Several MCDM methods are proposed to rank compromise solutions. A metaranking approach is used to rank compromise solutions.